Peptide scaffold‐derived peptidomimetic farnesyltransferase inhibitors. Issue 9 (7th June 2021) - Yang, Wei; Wang, Kuifeng; Wu, Hongwei; Shao, Hui; Chen, Huazhong; Zhu, Jiansheng
Abstract: Human protein farnesyltransferase (FTase) is involved in many essential signal transduction proteins and has been explored as druggable targets of diverse diseases such as cancer and inflammation. Here, we propose a new strategy termed as Peptide Scaffold‐derived Peptidomimetic FTase Inhibitors (PSPFI) to discover peptidomimetic lead molecular entities that can inhibit FTase. The strategy first defines a PSPFI‐oriented peptidomimetic library that contains >30, 000 sulfhydryl/thioether‐carrying peptidomimetics, and then employs molecular docking calculation, multiple similarity analysis, structural minimization, and affinity scoring to screen against the library, in order to discover those peptidomimetics that share high similarity with the core binding module (CBM) of FTase Rap2a peptide substrate in 2D‐chemistry, 3D‐conformation, pharmacophore, and nonbonded pattern, as well as exhibit high theoretical affinity to FTase. Totally 56 hit peptidomimetics were identified from the library, from which we manually select 6 structurally diverse, purchasable peptidomimetics to perform FTase assays. Consequently, four are determined as potent FTase inhibitors (IC50  < 1 μM); their inhibitory activity is moderately lower than the sophisticated FTase inhibitor Tipifarnib and considerably higher than the native CBM peptide. These peptidomimetic ligands share similar extended conformation, binding mode, and Zn 2+ coordination with Rap2a CBM peptide in FTase active site, but would have a different inhibition mechanism to Tipifarnib. Abstract : Based on multiple similarities with the core binding module of farnesyltransferase (FTase) Rap2a peptide substrate, an integrative strategy is described to screen against a Peptide Scaffold‐derived Peptidomimetic FTase Inhibitors‐oriented candidate library that contains a large number of sulfhydryl/thioether‐carrying peptidomimetics. The identified peptidomimetic compounds share similar extended conformation, binding mode, and Zn 2+ coordination with the substrate in FTase active site, but would have a different inhibition mechanism to Tipifarnib.